1997
DOI: 10.1101/gad.11.8.1048
|View full text |Cite
|
Sign up to set email alerts
|

GATA4 transcription factor is required for ventral morphogenesis and heart tube formation.

Abstract: Previous studies have suggested that the GATA4 transcription factor plays an important role in regulating mammalian cardiac development. In the studies described in this report we have used gene targeting to produce GATA4-deficient mice. Homozygous GATA4-deficient (GATA4-/-) mice died between 8.5 and 10.5 days post coitum (dpc). GATA4-/- embryos displayed severe defects in both rostral-to-caudal and lateral-to-ventral folding, which were reflected in a generalized disruption of the ventral body pattern. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
694
1
6

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 966 publications
(721 citation statements)
references
References 48 publications
20
694
1
6
Order By: Relevance
“…Furthermore, promoter analysis in transgenic mice and frogs has demonstrated that Gata factor consensus sites are required for the regulation of nkx2.5 expression (Searcy et al, 1998;Lien et al, 1999;Reecy et al, 1999;Sparrow et al, 2000). Even so, mice lacking any one of the gata4, gata5, or gata6 genes do not exhibit significant defects in cardiac patterning (Kuo et al, 1997;Molkentin et al, 1997Molkentin et al, , 2000Morrisey et al, 1998;Koutsourakis et al, 1999), suggesting some functional redundancy between Gata factors. Overall, these data strongly suggest conservation of Gata factor function during cardiac patterning in species ranging from insects to mammals.…”
Section: Conservation Of Patterning Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, promoter analysis in transgenic mice and frogs has demonstrated that Gata factor consensus sites are required for the regulation of nkx2.5 expression (Searcy et al, 1998;Lien et al, 1999;Reecy et al, 1999;Sparrow et al, 2000). Even so, mice lacking any one of the gata4, gata5, or gata6 genes do not exhibit significant defects in cardiac patterning (Kuo et al, 1997;Molkentin et al, 1997Molkentin et al, , 2000Morrisey et al, 1998;Koutsourakis et al, 1999), suggesting some functional redundancy between Gata factors. Overall, these data strongly suggest conservation of Gata factor function during cardiac patterning in species ranging from insects to mammals.…”
Section: Conservation Of Patterning Mechanismsmentioning
confidence: 99%
“…As in zebrafish, mouse mutants with severe endodermal deficiencies exhibit cardiac fusion defects. For example, mice lacking gata4 have dramatic reductions of endodermal tissue as well as cardiac fusion defects (Kuo et al, 1997;Molkentin et al, 1997). Furthermore, cardiac fusion can be rescued in gata4 mutant mice by reconstituting the endoderm (Narita et al, 1997).…”
Section: Conservation Of Morphogenesis Mechanismsmentioning
confidence: 99%
“…In mouse, loss of either GATA4 or GATA6 results in developmental arrest due to a requirement for these factors in the extraembryonic endoderm (Kuo et al, 1997;Koutsourakis et al, 1999). Studies using chimeras to circumvent this problem suggested that GATA4 has no evident function in cardiogenesis (Narita et al, 1997a) and that GATA6 is not required for specification of the myocardium (Kuo et al, 1997;Molkentin et al, 1997;Morrisey et al, 1998;Koutsourakis et al, 1999). In contrast, lossof-function studies in zebrafish and Xenopus show that GATA6 is required for the maintenance and differentiation of cardiac progenitors (Peterkin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Gata4 and Gata6 knock-out mice are embryonic lethal at E8.5-9.5 and E6.5-7.5, respectively, whereas Gata5 knock-out mice are viable. The embryonic lethality arises because of the defects in cardiogenesis and visceral endoderm formation, respectively (Kuo et al, 1997;Morrisey et al, 1998). Although originally thought to be selectively expressed in the heart and gastrointestinal tract, from these knock-out mouse data, the GATA-4-5-6 subfamily is now being identified in several other organ systems and disease states, including the central nervous system (CNS), where it is poorly characterized.…”
Section: Introductionmentioning
confidence: 99%